SMEs’ Drivers and Barriers to Decarbonisation in the East of England - Khosravi, Fatemeh; Jelliman, Sam; Uchendu, Chidinma (European Journal of Sustainable Development, 2023)
Most businesses in the UK have under 250 employees and thus count as SMEs. SMEs account for a significant proportion of greenhouse gas emissions and so there is a need for urgent action to be taken by SMEs in the journey to achieve net zero. This is currently recognised by SMEs as they are increasingly taking up decarbonisation actions, but their efforts are impeded by several barriers. Our research sought to provide insights into the barriers SMEs face when decarbonising business operations through an online survey and interview. Although our research confirms that financial constraints has been identified as the principal barrier to decarbonisation from SMEs perspectives, more than half of SMEs confirmed they lack the knowledge (34%, n=33) and skill (21%, n=20) was the main reason for not measing their carbon emission and starting their journey towards decarbonisation. Keywords: SMEs, Barriers, decarbonisation journey, Net Zero.